Influence of out-of-school sports/motor activity on school success - Pišot, Rado (Kinesiologia Slovenica, 2003)
Upon the sample of 2023 fourth class pupils of primary schools in the Gorenjska region (1048 boys and 975 girls) the relations between the participation in the out-of-school sports activities and success in school were studied. Data were collected by means of a questionnaire designed upon the data collected in previous studies (Petrović et al., 1998). The main aim of our research was to establish eventual statistically significant differences between the frequency of participation in out-of-school sports activities and the success in school as well as between the form of participation in out-of-school sports activities and the success in school. Statistically significant differences between the variables was verified by means of the chi-squared test. As statistically significant were considered differences between the variables presenting values of the Pearson's coefficient 0,05 and lower than 0,05. The research confirmed that statistically important differences do exist. Pupils who regularly participate in sports activities achieve a better learning success. Similarly, there is also a statistically significant differences between learning success and the form of sport activity. Pupils who train in sport clubs or under a trainers' supervision achieve a better success in school than those who participate in non-organised sports activities.
Keywords: gibalne dejavnosti; izvenšolske dejavnosti; osnovne šole; raziskave; učenci; učni uspeh